2013
DOI: 10.1117/12.2034113
|View full text |Cite
|
Sign up to set email alerts
|

Bag-of-visual-ngrams for histopathology image classification

Abstract: This paper describes an extension of the Bag-of-Visual-Words (BoVW) representation for image classification (IC) of histophatology images. This representation is one of the most used approaches in several high-level computer vision tasks. However, the BoVW representation has an important limitation: the disregarding of spatial information among visual words. This information may be useful to capture discriminative visual-patterns in specific computer vision tasks. In order to overcome this problem we propose t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…, k (1)-grams. Finally, it is worth knowing that we perform a set of specific experiments that highlights the general usefulness of visual n-grams, but a detailed study of the parameterization and other applications can be found in [10]. First Experiment: Table 2, thought the first row, shows the results of evaluating the traditional BoVW (Unigramas).…”
Section: Preliminary Results On Image Clasification Using Sequences Omentioning
confidence: 99%
“…, k (1)-grams. Finally, it is worth knowing that we perform a set of specific experiments that highlights the general usefulness of visual n-grams, but a detailed study of the parameterization and other applications can be found in [10]. First Experiment: Table 2, thought the first row, shows the results of evaluating the traditional BoVW (Unigramas).…”
Section: Preliminary Results On Image Clasification Using Sequences Omentioning
confidence: 99%
“…The use of visual codebooks as basis for summarizing images has seen a lot of applications since it has been initially proposed [30], being successfully used in analysis of digital pathology images as well [31,32]. Generally, the method requires constructing a dictionary of visual words (a codebook) that will be used as templates for summarizing the images.…”
Section: Bag Of Visual Wordsmentioning
confidence: 99%
“…In addition, we propose a genetic program to learn weighting schemes by combining a set of primitives. One should note that there are efforts for improving the bag of visual words in several directions, most notably, great advances have been obtained for incorporating spatial information [6], [4], [5], [17], [18]. The term-weighting schemes developed in this work can also be applied with the previous extensions.…”
Section: The Bag Of Visual Words Representationmentioning
confidence: 99%